Oleanane triterpene saponins with cardioprotective activity from Clinopodium polycephalum. Issue 7 (3rd July 2017) - Hu, Yu-Xia; Zhang, Wei; Zhang, Wen; Zhu, Yin-Di; Ma, Guo-Xu; Zhu, Nai-Liang; Sun, Wen; Ma, Ze-Xin; Yu, Shi-Chun; Xu, Xu-Dong; Chen, Kai-Tuo; Yang, Jun-Shan
Abstract: Two new triterpene saponins, clinopodiside VI (1 ) and saikosaponin c (2 ), along with six known saikosaponins (3 –8 ), were isolated from the plant of Clinopodium polycephalum. Compounds1 –3 showed moderate inhibition against H9c2 cell damage induced by H2 O2 .